The effect of specific exercises according to the (ATHOS EMG) readings of the percentage of participation of the muscles affecting the lifting of the (Bench Press) for the disabled powerlifting athletes - Watheq Taher; Eman Zaoun (التربية الرياضية, 2023)
The aim of the research is to identify the numerical values of the muscles working and affecting the lifting of the ((Bench Press)) and the percentage of their participation, as well as to identify the significance of the differences between the pre-tests and the post-tests for the disabled powerlifting players. The researchers used the one-group experimental approach due to its suitability to the nature of the study problem, and they chose the research community of the disable powerlifting player with for the sports season (2022/2023) and the (4) players representing the national Iraqi team for disable powerlifting, and they represented 100% of the research sample. They took a comprehensive enumeration method, and special tests were conducted on them in the powerlifting and weightlifting hall of the Iraqi National Paralympic Committee, and after analyzing and discussing the results, the two researchers concluded that there are significant differences between the pre and post tests and in favor of the post tests for the research group because of the specific exercises prepared for this purpose. based on that, the two researchers recommend conducting extensive studies of this sport event and paying attention to studying the working muscles directly for the players in order to avoid their exposure to injury and avoid Waste of time and effort, as well as knowing the level of force production with these muscles and see it depending on the size of the muscle to increase the proportion of its participation in the lift